SOCIAL COOPERATION WITHIN VIRTUAL WORLDS. OLD SOCIAL PHENOMENA EMERGING IN NEW ENVIRONMENTS - RICHARDS, Diana; DECU, Andrei (Studia Universitatis Babeș-Bolyai Philosophia, 2017)
The world we live in is expanding its borders by letting the virtual become part of our lives. Digitisation equally pervades the public and the private sectors and transforms interactions between individuals, and between individuals and the state. For instance, the UK government is now in the process of digitising a whole range of processes and interactions with its citizens, through the Governmental Digital Service (GDS). In this article we aim to prove that virtual worlds provide a playground for social engineers, legal researchers and philosophers, for two reasons. First, virtual worlds offer confirmations of social theories of cooperation, they illustrate that cooperation among individuals emerges spontaneously where there are no established forms of governance and decision. Secondly, virtual worlds offer sandboxes where the peculiarities of online interaction can be observed.